A clinical comparative study on three surgical approaches for the removal of impacted supernumerary teeth in the midline area of the anterior maxilla - CHENG Xu, ZHENG Xianyu, DING Ding, HUANG Shanshan, WU Xiaoting, ZHANG Hengguo (Kouqiang yixue)
Objective To evaluate the efficacy and safety of different surgical approaches for extracting high-positioned supernumerary teeth in the maxillary anterior midline region. Three surgical methods, the labial approach, the palatal approach, and a longitudinal incision beside the upper lip frenum were compared. Methods A total of 102 patients were recruited from the Department of Oral and Maxillofacial Surgery at the Affiliated Stomatological Hospital of Anhui Medical University between January and September 2024. They were randomly assigned via a random-digit table to three groups: the labial approach group (n=32), the palatal approach group (n=34), and the longitudinal incision beside the upper lip frenum group (n=36). Operation time, bone removal volume, postoperative midfacial swelling, degree of pain, and patient satisfaction across the three groups were recorded and compared. Results The average operation time in the labial approach group ((20.50±3.02) min) and the longitudinal incision group ((21.66±2.31) min) were both significantly shorter than that in the palatal approach group ((29.19±3.40) min). In contrast, the palatal approach group demonstrated markedly lower postoperative swelling and pain scores (P< 0.05), along with the highest patient satisfaction, as reflected in the OHIP-14 scale. However, the palatal approach required the greatest bone removal volume, measuring (91.19 ± 9.86)mm3. Conclusion Despite the palatal approach yielding superior outcomes in terms of postoperative pain control, swelling reduction, and patient satisfaction, it necessitated longer operation time and involved greater bone removal. Meanwhile, the labial approach and the longitudinal incision beside the upper lip frenum were comparable in all measured parameters, showing no statistically significant differences. Therefore, when extracting high midline impacted teeth in the maxillary anterior region, the choice of surgical approach should balance safety, minimal invasiveness, and patient satisfaction.